International profit shifting within multinationals : a multi-country perspective - Huizinga, Harry; Laeven, Luc.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This study models the opportunities and incentives generated by international tax differences for international profit shifting by multinationals. Unlike previous studies, consideration is made not only of profit shifting arising from international tax differences between affiliates and parent companies, but also from tax differences between affiliates in different host countries. The model yields the prediction that a multinational's profit shifting in a country depends on a weighted average of international tax rate differences between all countries where the multinational is active. Using a unique dataset containing detailed firm-level information on the parent companies and subsidiaries of European multinationals and detailed information about the international tax system, the model is tested and the extent of intra-European profit shifting by European multinationals is empirically examined. On average, what is found is a semi-elasticity of reported profits with respect to the top statutory tax rate of 1.43, while shifting costs are estimated to be 1.6 percent of the tax base. International profit shifting leads to a substantial redistribution of national corporate tax revenues.
Economic Papers